Application of Key Technologies of Cloud Computing Energy Saving in IT Support System - Zhang, Bochao (Journal of Artificial Intelligence and Information, 2025)
This article introduces cloud computing technology, analyzes the application principles of energy-saving key technologies in cloud computing for IT support systems, and dissects the practical energy efficiency of these key technologies. By examining cloud-based business scenarios and analyzing the basis and algorithms for resource scheduling, intelligent power management contributes to reducing host power consumption during data center operation. The computational demands of business operations are positively correlated with energy consumption, and these demands can vary due to business requirements. Creating an energy-saving scheduling model and implementing it within the IT support cloud platform helps address energy-saving and emission reduction issues in cloud computing. Furthermore, the key energy-saving technologies in cloud computing enable flexible implementation of resource scheduling.